The Possible Preventative Role of Lactate- and Butyrate-Producing Bacteria in Colorectal Carcinogenesis - Song, Chin-Hee; Kim, Nayoung; Nam, Ryoung Hee; Choi, Soo In; Jang, Jae Young; Kim, Eun Hye; Choi, Jina; Choi, Yonghoon; Yoon, Hyuk; Lee, Sun Min; Seok, Yeong-Jae (Gut and liver, 2024)
: The gut microbiome has emerged as a key player that mechanistically links various risk factors to colorectal cancer (CRC) etiology. However, the role of the gut microbiome in CRC pathogenesis remains unclear. This study aimed to characterize the gut microbiota in healthy controls (HCs) and patients with colorectal adenoma (AD) and CRC in subgroups based on sex and age. : Study participants who visited the hospital for surveillance of CRC or gastrointestinal symptoms were prospectively enrolled, and the gut microbiome was analyzed based on fecal samples. : In terms of HC-AD-CRC sequence, commensal bacteria, including lactate-producing ( ) and butyrate-producing ( ) bacteria, were more abundant in the HC group than in the AD and CRC groups. In the sex comparison, the female HC group had more lactate-producing bacteria ( and ) than the male HC group. In age comparison, younger subjects had more butyrate-producing bacteria ( and ) than the older subjects in the HC group. Interestingly, lactate-producing bacteria ( ) were more abundant in females than males among younger HC group subjects. However, these sex- and age-dependent differences were not observed in the AD and CRC groups. : The gut microbiome, specifically lactate- and butyrate-producing bacteria, which were found to be abundant in the HC group, may play a role in preventing the progression of CRC. In particular, lactate-producing bacteria, which were found to be less abundant in healthy male controls may contribute to the higher incidence of CRC in males.